2016
DOI: 10.1177/0033354916669497
|View full text |Cite
|
Sign up to set email alerts
|

A Scan of CDC-Authored Articles on Legal Epidemiology, 2011-2015

Abstract: Results of the scan can be used to identify opportunities for the agency to better support research, professional development, networking, publication, and tracking of publication in this emerging field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Of these, 11 states required dementia training for all licensed settings; six states required this training in some, but not all license types; and 11 states specified the training was only necessary for dementia-designated care settings. As shown in Figure 1, by 2018, 41 states (80%) had either requirements for all settings (14), some licensed settings (10), or only dementia-designated settings (17). In comparison, a 2015 legal review of dementia-specific initial training for direct care workers identified 21 states (41%) with these requirements, in either all settings (6) or only for dementia "special care" units (15).…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 11 states required dementia training for all licensed settings; six states required this training in some, but not all license types; and 11 states specified the training was only necessary for dementia-designated care settings. As shown in Figure 1, by 2018, 41 states (80%) had either requirements for all settings (14), some licensed settings (10), or only dementia-designated settings (17). In comparison, a 2015 legal review of dementia-specific initial training for direct care workers identified 21 states (41%) with these requirements, in either all settings (6) or only for dementia "special care" units (15).…”
Section: Re Sultsmentioning
confidence: 99%
“…11 For example, hospitals, or units within hospitals, might serve patients with acute, traumatic, long-term, or mental health needs, or patients who are indigent. 12,13 Studies have used legal epidemiology 14 and health policy methodologies 15,16 to document the influence of policies using the state as the unit of analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broader economic security policies such as the Earned Income Tax Credit have been shown to be independently associated with measures of child development (Dahl and Lochner 2012; Hamad and Rehkopf 2016). Despite the relationship between such policies and developmental outcomes, and support for evidence-informed policy within children’s mental health systems (Miles et al 2010), empirical study of how laws influence access to mental health services has been infrequent (Martini et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…12 A scan of CDC-authored articles on legal epidemiology, the scientific study of law as a factor in the cause, distribution, and prevention of disease (also known as public health law research, which includes policy surveillance research), identified few legally trained authors on teams conducting legal epidemiology research "despite the interdisciplinary quality of CDC's staff members and work." 13 The review did not identify any policy studies in STD prevention that used mixed methods.…”
mentioning
confidence: 99%